Table ST6 from ROS Induction Targets Persister Cancer Cells with Low Metabolic Activity in NRAS-Mutated Melanoma - Ossia M. Eichhoff (14964145) (2025)
Table ST6: Differential expressed lipids and their FDRs in sensitive vs resistant cells (negative values are upregulated in sensitive cells).